Scorpion Sting Associated with Cellulitis and Bradycardia: A Case Report - Chand, Sharad (Indian Journal of Pharmacy Practice)
Scorpion stings are so frequent complaints as like other bites across the globe and it is one of the more common causes of hospitalization in the rural India. Normally, the stings will lead to the intense pain but having less mortality compare to another stings and bites, around 30% of untreated cases may proceed to serious clinical conditions like Bradycardia, Arrhythmia, Pain, Loss of function in bitten area. The life-threatening complications of myocarditis and pulmonary oedema are known in red scorpion in India Hence, The case is reported to emphasize the proper management of scorpion especially in the rural areas.
Keywords: Scorpion sting; Bradycardia; Scorpion sting shock; Managing stings; Cellulitis in Stings.